Is intramedullary screw fixation biomechanically superior to locking plate fixation and/or tension band wiring in transverse olecranon fractures? A cadaveric biomechanical comparison study. Issue 4 (April 2020) - Hahn, Alexander; O'Hara, Nathan N.; Koh, Kyung; Zhang, Li-Qun; O'Toole, Robert V.; Andrew Eglseder, W.
Highlights: Intramedullary screw, locking plate, and tension band wire fixation are three techniques used to fix transverse olecranon fractures, and we compared their clinically important mechanical properties in a cadaveric model. No statistically significant difference was observed in fracture compression among intramedullary screw, locking plate, and tension band fixation methods. Intramedullary screw and locking plate fixation techniques led to 0% implant failure. Tension band fixation led to 100% implant failure. Although there are no statistically significant differences in compression across the fracture site among the three techniques compared, a much higher risk of implant failure occurred with tension band fixation. Abstract: Objectives: To compare clinically important mechanical properties of three techniques used to fix transverse olecranon fractures (Arbeitsgemeinschaft fur Osteosynthesefragen and Orthopaedic Trauma Association class 2U1B1): (1) intramedullary (IM) screw, (2) locking plate, and (3) tension band wire in a realistic loading protocol using a cadaveric model. Methods: Fresh frozen cadaveric transverse olecranon fracture models were fixed with an IM screw ( n = 6), a locking plate ( n = 6), or a tension band ( n = 6). Compression after fixation was recorded using a pressure sensor in the fracture before samples were loaded through the triceps tendon for 500 cycles of 0–500 N, assessing implant survival. The primary outcome measure was compression force before loading. The secondary outcome was frequency of implant failure defined as breakage of the implant itself or fracture gapping >5 mm. Binary outcomes were compared with χ 2, and continuous variables were compared with unadjusted analysis of variance and a multivariable regression model adjusting for age, sex, dual-energy X-ray absorptiometry T-score, and testing order. Results: No statistically significant difference was shown in fracture compression between IM screw (mean, 162 N; 95% confidence interval [CI], 27–297 N), locking plate (mean, 125 N; 95% CI, −9–260 N), and tension band (mean, 163 N; 95% CI, 29–298 N) in unadjusted ( p = 0.89) and adjusted ( p = 0.82) analyses. A 100% implant failure rate was observed with tension band compared with 0% implant failure with IM screw or locking plate ( p < 0.01). Conclusion: We found no statistically significant differences in compression across the fracture site among techniques. We did find a higher risk of implant failure with tension band compared with IM screw and locking plate during cyclic loading in cadaveric bone.